Transactional and transformational leadership impacts on organizational learning - Hugo Zagorsek; Vlado Dimovski; Miha Skerlavaj (Journal for East European Management Studies, 2009)
This study empirically relates two important areas of management research: the full-range theory of leadership and the organizational learning process. Specifically, this contribution addresses three issues: (1) the impact of transformational leadership and (2) of transactional leadership on the organizational learning process and (3) whether the influence of transformational leadership is stronger than of a transactional type of leadership. The results show that transformational leadership has a strong impact on all four constructs of organizational learning. A direct impact is evident only regarding information acquisition and behavioural and cognitive changes. – – Die vorliegende Studie bezieht sich auf zwei wichtige Bereiche der Managementforschung: Die Führungstheorie und den Prozess des organisationalen Lernens. Insbesondere befasst sich der Beitrag mit drei Themen: (1) der Auswirkung transformationalen Führung und (2) der Auswirkung transaktionaler Führung auf den organisatorischen Lernprozess sowie (3) ob der Einfluss der transformationalen Führung stärker ist als der Einfluss einer transaktionalen Führung. Die Ergebnisse zeigen, dass die transformationale Führung einen starken Einfluss auf alle vier Kontrukte organisationalen Lernens hat. Ein direkter Einfluss wird nur im Hinblick auf Informationsbeschaffung und Verhaltens- und Kognitionsveränderungen sichtbar.
Keywords: 650; Transactional leadership; transformational leadership; organizational learning process